Effects of nano-Rhodiola rosea combined with treadmill exercise on anti-exercise fatigue in rats - Wang, Jibing; Zhang, Guoyan; Wang, Duona; Yan, Yuanyuan; Yang, Qin (Frontiers in Nutrition, 2024)
OBJECTIVE: To explore the potential strategies and mechanisms for enhancing the bioavailability of Rhodiola rosea. METHODS: 36 Sprague-Dawley rats(8-weeks-old) were randomly assigned to six groups (n=6 per group). Groups Ⅰ and Ⅱ received nano-dose forms of R rosea, groupsⅢ and Ⅳ received normal dose form of R rosea, and groups Ⅴ and Ⅵ served as distilled water control groups. Groups II, IV, and VI were combined with moderateintensity treadmill exercise. Each group received a daily gavage with 0.5 ml of nano -R rosea solution (0.01 mg/ml), normal R rosea solution, and distilled water. All rats were subjected to exhaustive swimming after 4 weeks. Outcome measures include GSH-px activity, T-AOC activity, MDA content, hepatic glycogen content, and T-SOD activity.RESULTS: For plasma MDA content, group I was lower than group III (p<0.01) and group V (p<0.01), group II was lower than group III (p<0.01), group VI was higher than group II (p<0.05) and group IV (p<0.05). For plasma T-AOC activity, group II was higher than group VI (p<0.01). For plasma GSH-px activity, group I was lower than group IV (p<0.05), groups II, III, and IV were higher than group V (p<0.05), and group V was lower than that of group VI (p<0.05). For T-SOD activity of quadriceps muscle, groups I and III were higher than that in group V (p<0.05).CONCLUSION: R rosea has a positive effect on anti-exercise fatigue in rats, with the nano-dosage form of R rosea showing more significant efficacy than the normal form especially combined with aerobic exercise.